2016
DOI: 10.14440/bladder.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the MB49 syngeneic, murine model of bladder cancer

Abstract: OBJECTIVEThe MB49 syngeneic, murine model of bladder cancer has been widely used for more than 35 years. In humans, bladder cancer is one third as prevalent in women as in men, with a trend toward lower prevalence in parous compared to nulliparous women. Our objective was to determine if the MB49 bladder cancer model reproduces the sex differences observed in humans, and to determine its sensitivity to testosterone and the pregnancy hormone, human chorionic gonadotropin (hCG).METHODSMale and female C57BL/6 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…We found that even at low cell numbers, differential tumor growth in male mice was not significant between CSCs and parental cells, owing to the development of larger tumors from parental cells in male mice as compared to female littermates. These findings are in line with the report by White-Gilbertson and colleagues who showed sex-mediated disparity in growth of xenotransplanted bladder cancer cells (39). It is noteworthy that epidemiological and clinical studies have previously demonstrated that men are at a greater risk of developing lung cancer than women and relatively display poorer clinical outcomes (40).…”
Section: Discussionsupporting
confidence: 93%
“…We found that even at low cell numbers, differential tumor growth in male mice was not significant between CSCs and parental cells, owing to the development of larger tumors from parental cells in male mice as compared to female littermates. These findings are in line with the report by White-Gilbertson and colleagues who showed sex-mediated disparity in growth of xenotransplanted bladder cancer cells (39). It is noteworthy that epidemiological and clinical studies have previously demonstrated that men are at a greater risk of developing lung cancer than women and relatively display poorer clinical outcomes (40).…”
Section: Discussionsupporting
confidence: 93%
“…To assess the contribution of adaptive immunity to sex bias, we compared MB49 growth in male and female wild type (WT) mice, as well as mice with a deficiency of T cells ( Tcrb/Tcrd −/− ), B cells ( Ighm −/− ) or both ( Rag2 −/− ). Consistent with an earlier report 14 , MB49 grew more aggressively in WT male versus female mice ( Fig. 1a ).…”
Section: Cd8+ T Cell Immunity Is Required For Sex Differences In Murisupporting
confidence: 92%
“…Male bias in bladder cancer can be modeled successfully in mice with N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN)-induced cancer 12,13 and a transplantable syngeneic bladder cancer cell line MB49 14 . To assess the contribution of adaptive immunity to sex bias, we compared MB49 growth in male and female wild type (WT) mice, as well as mice with a deficiency of T cells ( Tcrb/Tcrd −/− ), B cells ( Ighm −/− ) or both ( Rag2 −/− ).…”
Section: Cd8+ T Cell Immunity Is Required For Sex Differences In Murimentioning
confidence: 99%
“…The MB49 cell line is a useful in vivo murine model of bladder cancer that has several similarities to human disease (14). MB49 tumors in mice are sensitive to treatment with the antituberculosis vaccine bacillus Calmette–Guérin (15, 16), an immunotherapy for treatment of early-stage bladder cancer that is thought to activate the immune system to slow tumor growth.…”
mentioning
confidence: 99%
“…MB49 tumors in mice are sensitive to treatment with the antituberculosis vaccine bacillus Calmette–Guérin (15, 16), an immunotherapy for treatment of early-stage bladder cancer that is thought to activate the immune system to slow tumor growth. To evaluate different aspects of disease, MB49 cells can be administered to mice via various routes, including transurethral, s.c. or i.v., leading to development of tumors and spontaneous lung metastasis within 3 wk (14, 16–18). …”
mentioning
confidence: 99%